Dual-Function Analysis of Astaxanthin on Golden Pompano (Trachinotus ovatus) and Its Role in the Regulation of Gastrointestinal Immunity and Retinal Mitochondrial Dysfunction Under Hypoxia Conditions - Niu, Jin; Zhao, Wei; Lu, Dan-Qi; Xie, Jia-Jun; He, Xuan-Shu; Fang, Hao-Hang; Liao, Shi-Yu (Frontiers in Physiology, 2020)
The present study investigated the potential mechanisms of astaxanthin in the regulation of gastrointestinal immunity and retinal mitochondrial function of golden pompano (Trachinotus ovatus). Triplicate groups of juvenile T. ovatus were fed one of six diets (D1, D2, D3, D4, D5 and D6) for 8 weeks, with each diet containing various concentrations of astaxanthin (0%, 0.0005%, 0.001%, 0.005%, 0.01%, or 0.1%, respectively). Growth performance of fish fed the D2-D5 diets were higher than that of fish fed the D1 diet; however, growth performance and survival of fish deteriorated sharply in fish fed the D6 diet. Gut villus in fish fed the D2-D5 diets were significantly longer and wider than that of fish fed the D6 diet. Feeding with D2-D5 diets led to increased abundance of Bacillus, Pseudomonas, Oceanobacillus, Lactococcus, Halomonas, Lactobacillus and Psychrobacter while abundance of Vibrio and Bacterium decreased. Additionally, feeding with the D6 diet resulted in a sharp decline in Pseudomonas and Lactobacillus abundance and a sharp increase in Vibrio abundance. A low dissolved oxygen environment (DO, 1.08 mg/L) was conducted for 10 hours after the rearing trial. No fish mortality was observed for any of the diet treatments. Lysozyme (LYZ) activity in fish fed the D6 diet decreased sharply and was significantly lower than that in other groups. ROS production also decreased sharply in fish fed the D6 diet. Moreover, the conjunctiva and sclera in the fish fed the D6 diet were indistinguishable. Suitable dietary astaxanthin supplementation levels (0.005%-0.1%) exerted a neuroprotective effect from low dissolved oxygen environments is due to up-regulated expression of anti-apoptotic factors, such as phosphorylated Bcl-2-associated death promoter (pBAD), phosphorylated glycogen synthase kinase-3β (pGSK-3β), Bcl-2 extra large (Bcl-xL), and down-regulated expression of Bcl-2 associated X protein (Bax) pro-apoptotic factor in retinas. Furthermore, suitable dietary astaxanthin levels (0.0005%-0.01%) suppressed up-regulation of critical mitochondrial components, such as peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), mitochondrial transcription factor A (TFAM), and mitochondrial DNA (mtDNA). While excessive astaxanthin supplementation produces the opposite effect. Second-degree polynomial regression of WG indicated that the optimum dietary astaxanthin for juvenile T. ovatus is 0.049%.